Antimelanogenic and Antimigration Properties of the Ethyl Acetate Fraction of Calendula officinalis Flowers on Melanoma Cells. (4th January 2019) - Xuan, Song Hua; Park, Young Min; Park, Soo Nam
Abstract: Calendula officinalis L., commonly known as marigold, is not only cultivated for ornamental purposes but is also used as a traditional medicinal herb. Its flowers have been used to treat various skin diseases, including rashes, burns, cuts and bruises, since ancient times. However, to our knowledge, the impact of C. officinalis L. on melanoma and its mechanism have not been clarified. The aim of this work was to investigate the chemical characterization and antimelanogenic and antimigration activities of the ethyl acetate fraction of C. officinalis flowers (EFC), as well as elucidate the potential mechanism. The obtained results showed that EFC markedly decreased α ‐MSH‐induced melanin production and the cell migration ability of melanoma cells in a dose‐dependent manner. Additionally, EFC significantly inhibited the activity and expression of matrix metalloproteinase 2 (MMP‐2) via suppressing the mitogen‐activated protein kinase (MAPK) signaling pathway. Taken together, the present study demonstrated that C. officinalis flowers can be used as a natural source of antimelanogenisis and antimigration regent to treatment or prevent skin diseases. Abstract : The ethyl acetate fraction of Calendula officinalis flowers (EFC) can inhibit the melanin production and migration of melanoma cells. The possible mechanism underlying its antimigration effect is the downregulation of MMP‐2 activity and expression by the suppression of MAPK phosphorylation. Overall, our results provide evidence for the molecular mechanism of C. officinalis in the treatment or prevention of skin diseases.